2018
DOI: 10.1007/s00572-018-0821-4
|View full text |Cite
|
Sign up to set email alerts
|

Ecological responses to forest age, habitat, and host vary by mycorrhizal type in boreal peatlands

Abstract: Despite covering vast areas of boreal North America, the ecological factors structuring mycorrhizal fungal communities in peatland forests are relatively poorly understood. To assess how these communities vary by age (younger vs. mature), habitat (fen vs. bog), and host (conifer trees vs. ericaceous shrub), we sampled the roots of two canopy trees (Larix laricina and Picea mariana) and an ericaceous shrub (Ledum groenlandicum) at four sites in northern Minnesota, USA. To characterize the specific influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…Mycorrhizal colonization rate, species richness, and spore density were dependent on the identity of tree species'. This finding concurs with other studies reporting that the host plant affects the composition and diversity of AM fungal communities across various ecosystems, including deserts, tropical zones, and peatlands [11,16,44]. Such effects may arise from differences in fundamental traits of host plants, such as the root morphology and structure of tree species [45,46], which could have affected the likelihood of mycorrhizal formation among fungal taxa.…”
Section: Effects Of Tree Species On Am Fungisupporting
confidence: 91%
“…Mycorrhizal colonization rate, species richness, and spore density were dependent on the identity of tree species'. This finding concurs with other studies reporting that the host plant affects the composition and diversity of AM fungal communities across various ecosystems, including deserts, tropical zones, and peatlands [11,16,44]. Such effects may arise from differences in fundamental traits of host plants, such as the root morphology and structure of tree species [45,46], which could have affected the likelihood of mycorrhizal formation among fungal taxa.…”
Section: Effects Of Tree Species On Am Fungisupporting
confidence: 91%
“…in this peatland (Kennedy et al . ), it is plausible to expect increased non‐melanised necromass inputs that are highly labile compared to the recalcitrant inputs produced by Cenococcum geophilum . These host‐mediated responses to warming, along with those of the ericaceous shrubs, may also play a key role in determining the amount of necromass C that is quickly mineralised versus the amount entering stable belowground C pools.…”
Section: Discussionmentioning
confidence: 99%
“…and Larix laricina (Du Roi) K. Koch, both of which are well‐colonised by EM fungi at the site (Kennedy et al . ). The understory shrub communities are primarily composed of ericaceous shrubs such as Rhododendron groenlandicum Oeder and Chamaedaphne calyculata (L.) Moench that all host ERM fungi (Kennedy et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In our study, the presence of ericaceous shrubs (associated with ericoid fungi) close to fir saplings rather affected their root EMF communities than reduced the ramification index. Numerous studies have already shown how ericaceous shrubs affect EMF communities associated with trees, such as red oak ( Quercus rubra L.), hemlock (Walker et al, 1999), pine ( Pinus strobus L., P. sylvestris L.) (Kohout et al, 2011), and black spruce (Yamasaki et al, 1998; Kennedy et al, 2018). In the boreal forest, ericaceous shrubs not only compete with fir growth and nutrition, but also modify forest dynamics and lead to thick accumulation of soil organic matter and soil acidification.…”
Section: Discussionmentioning
confidence: 99%